2022
DOI: 10.1001/jamanetworkopen.2022.40612
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Use of Opioids vs Nonpharmacologic Treatments in Adults With Pain, 2011-2019

Abstract: ImportanceChronic pain prevalence among US adults increased between 2010 and 2019. Yet little is known about trends in the use of prescription opioids and nonpharmacologic alternatives in treating pain.ObjectivesTo compare annual trends in the use of prescription opioids, nonpharmacologic alternatives, both treatments, and neither treatment; compare estimates for the annual use of acupuncture, chiropractic care, massage therapy, occupational therapy, and physical therapy; and estimate the association between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…One recent analysis of the Medical Expenditure Panel Survey (2011–2019) found that female sex and higher levels of education and family income were associated with increased odds of visiting nonpharmacologic providers (eg, acupuncturists and physical therapists) rather than using opioids. 6 Older age, non-White race, Hispanic ethnicity, and having higher levels of pain interference and comorbidities were associated with lower odds of visiting nonpharmacologic providers exclusively. 6 Other studies have found that younger age, female sex, non-Hispanic (NH) White race/ethnicity, and higher levels of education, income, and pain limitations are associated with increased odds of IHM use among subjects with chronic pain, 8 low back or neck pain, 9 , 14 and arthritis.…”
Section: Introductionmentioning
confidence: 92%
“…One recent analysis of the Medical Expenditure Panel Survey (2011–2019) found that female sex and higher levels of education and family income were associated with increased odds of visiting nonpharmacologic providers (eg, acupuncturists and physical therapists) rather than using opioids. 6 Older age, non-White race, Hispanic ethnicity, and having higher levels of pain interference and comorbidities were associated with lower odds of visiting nonpharmacologic providers exclusively. 6 Other studies have found that younger age, female sex, non-Hispanic (NH) White race/ethnicity, and higher levels of education, income, and pain limitations are associated with increased odds of IHM use among subjects with chronic pain, 8 low back or neck pain, 9 , 14 and arthritis.…”
Section: Introductionmentioning
confidence: 92%
“…Author affiliations and article information are listed at the end of this article. Therefore, I read with anticipation the study by Pritchard and colleagues, 9 which promised to present nationally representative trends over time in the concomitant use of opioids and NPAs. The authors, using data from the Medical Expenditure Panel Survey (MEPS), were able to identify whether participants used opioids for their pain, NPAs for this pain, both, or no treatment (ie, neither opioids nor NPAs).…”
Section: + Related Articlementioning
confidence: 99%
“…Pritchard and colleagues noted that 5.6% of all participants with pain reported using both opioids and NPA. Although this percentage is less than that seen by Vanneman, et al (15%), Pritchard and colleagues found higher concomitant use of opioids and NPAs in individuals with postsurgical pain (12.7%) vs those with nonsurgical pain (3.7%). Notably, although the postsurgical group saw a substantial increase in concomitant use of opioids and NPAs between 2011 and 2019, this increase was not seen in the nonsurgical group.…”
mentioning
confidence: 96%
See 2 more Smart Citations